Adiponectin: A player in the pathogenesis of hormone-dependent cancers - Tsankof, Alexandra; Tziomalos, Konstantinos (Frontiers in Endocrinology, 2022)
Hormone-dependent cancers are a major cause of morbidity and mortality in both genders. Accumulating evidence suggest that adiponectin, an adipokine with multifaceted functions, is implicated in the pathogenesis of several malignancies. In the present review, we discuss the existing data regarding this relationship. Several observational studies showed that low adiponectin levels are associated with higher risk for breast, cervical, endometrial, ovarian and prostate cancer. A relationship between adiponectin and the aggressiveness of some of these tumors has also been reported. In vitro studies reported that adiponectin inhibits the proliferation and induces apoptosis of breast, cervical, endometrial, ovarian and prostate cancer cells. Given the high prevalence of these cancers and the substantial associated morbidity and mortality, the role of agents that increase adiponectin levels and/or stimulate its activity should be evaluated for the prevention and management of these common tumors.